2010
DOI: 10.1200/jco.2009.27.5933
|View full text |Cite
|
Sign up to set email alerts
|

Is Mammographic Breast Density a Breast Cancer Risk Factor in Women With BRCA Mutations?

Abstract: Increased mammographic breast density is not associated with higher breast cancer incidence in women with BRCA mutations. On the basis of these findings, density should not be considered a factor for these women in decision making regarding prophylactic surgery or chemoprevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 21 publications
2
25
0
Order By: Relevance
“…The two largest studies, both retrospective (Mitchell et al 2006, Ramon et al 2015 with sample sizes of 206 and 691 mutation carriers (including 96 and 248 affected women, respectively) found that mammographic density is an independent risk factor for breast cancer in both BRCA1 and BRCA2 mutation carriers with similar magnitudes of association to those observed in the general population (RR: 2.30 for density ≥50% vs <50%). However, a nested case-control study of mutation carriers that included a much smaller number (N = 46) of cases, all incident (Passaperuma et al 2010), found no evidence of association. Although the balance of evidence suggests that mammographic density is likely to also be a breast cancer risk factor for BRCA1 and BRCA2 mutation carriers, additional and larger studies are required to fully characterise the associations.…”
Section: Mammographic Densitymentioning
confidence: 96%
See 1 more Smart Citation
“…The two largest studies, both retrospective (Mitchell et al 2006, Ramon et al 2015 with sample sizes of 206 and 691 mutation carriers (including 96 and 248 affected women, respectively) found that mammographic density is an independent risk factor for breast cancer in both BRCA1 and BRCA2 mutation carriers with similar magnitudes of association to those observed in the general population (RR: 2.30 for density ≥50% vs <50%). However, a nested case-control study of mutation carriers that included a much smaller number (N = 46) of cases, all incident (Passaperuma et al 2010), found no evidence of association. Although the balance of evidence suggests that mammographic density is likely to also be a breast cancer risk factor for BRCA1 and BRCA2 mutation carriers, additional and larger studies are required to fully characterise the associations.…”
Section: Mammographic Densitymentioning
confidence: 96%
“…Data from population-based studies also suggest that mammographic density is a risk factor for both ER-positive and ER-negative breast cancer (Bertrand et al 2013), although some studies found associations only with ER-positive disease. Only three studies have investigated the association between mammographic density and breast cancer risk for BRCA1 and BRCA2 mutation carriers (Mitchell et al 2006, Passaperuma et al 2010, Ramon et al 2015. The two largest studies, both retrospective (Mitchell et al 2006, Ramon et al 2015 with sample sizes of 206 and 691 mutation carriers (including 96 and 248 affected women, respectively) found that mammographic density is an independent risk factor for breast cancer in both BRCA1 and BRCA2 mutation carriers with similar magnitudes of association to those observed in the general population (RR: 2.30 for density ≥50% vs <50%).…”
Section: Mammographic Densitymentioning
confidence: 99%
“…However variations in the pattern and magnitude of parenchymal enhancement did emerge: women under 45 years of age with increased breast density exhibited more nodular and heterogeneous PEP and also a stronger magnitude of enhancement (E 1 , E peak ) compared with women with lower density breasts. The implications of this finding are not clear, as the significance of breast tissue density within a high risk cohort is not well established [29]. Additionally, our assessment of breast density was based on T 2 weighted MRI rather than x-ray mammograms.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study also demonstrated a moderately high positive association between the risk prediction scores generated by the mammographic density related image feature analysis and the actual risk of women having an image-detectable breast cancer in the next subsequent examinations [10]. Despite that mammographic density has the highest discriminatory power besides women’s age in the existing epidemiology-based risk models [6], its discriminatory power at the individual level remains low and controversial [15,16]. …”
Section: Introductionmentioning
confidence: 99%